2014
DOI: 10.3747/co.21.1855
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Perspective on the Safe Administration of Bendamustine and the Prevention and Management of Adverse Events

Abstract: Although bendamustine has been used to treat lymphoproliferative disorders for decades, it has only recently been approved for use in Canada. Thus, Canadian recommendations on the administration of bendamustine and the management of common adverse events (aes ) are needed. This article highlights effective management and assessment strategies recommended by Canadian nurses and pharmacists for the most common aes arising from the use of bendamustine in patients with chronic lymphocytic leukemia and indolent non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Moreover, the incidence of neutropenia-the only grade 3 or 4 teae resulting in dose delay-was higher in patients on the 21-day cycle (25%) than in those on the 28-day cycle (6.9%). Taken together, those results might provide support for use of the 28-day treatment cycle, which is routine with bendamustine in many treatment centres across Canada for the management of inhl 37 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Moreover, the incidence of neutropenia-the only grade 3 or 4 teae resulting in dose delay-was higher in patients on the 21-day cycle (25%) than in those on the 28-day cycle (6.9%). Taken together, those results might provide support for use of the 28-day treatment cycle, which is routine with bendamustine in many treatment centres across Canada for the management of inhl 37 .…”
Section: Discussionmentioning
confidence: 91%
“…A paper by Koolwine et al 37 suggested that a shorter bendamustine infusion time might increase peak plasma levels, resulting in more frequent nausea. The authors recommended giving bendamustine to all patients in a 60-minute infusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravenous rituximab in combination with CVP was only approved for use as first-line therapy in the treatment of NHL by Health Canada on 20 December 2005 and as maintenance treatment on 28 July 2006, part way through the study period. Bendamustine in combination with rituximab received a Health Canada notice of compliance for use in the relapsed setting in August 2012 and public reimbursement in Ontario in May 2013 and then moved into use in the first-line setting [29]. In 2018, a subcutaneous preparation of rituximab was approved as a fixed dose for combination therapy, simplifying administration and reducing systemic therapy suite time [8], with a corresponding reduction in costs related to administration.…”
Section: Discussionmentioning
confidence: 99%